Rifabutin‐based High‐dose Proton‐pump Inhibitor and Amoxicillin Triple Regimen as the Rescue treatment for Helicobacter pylori. Issue 6 (18th September 2014) - Lim, Hyun Chul; Lee, Yong Jae; An, Byoungrak; Lee, Seung Woo; Lee, Yong Chan; Moon, Byung Soo
Abstract: Background: Rifabutin has been known to be effective in multidrug‐resistant Helicobacter pylori ‐harboring patients undergoing treatment failure for H. pylori infection. Aim: To evaluate the efficacy of 7‐day treatment regimen consisting rifabutin daily but increasing the dose of amoxicillin and lansoprazole in patients who have failed first and second eradication and to assess the side effect profiles in South Korea. Methods: From December 2007 to May 2013, 59 H. pylori ‐infected patients with two previous eradication failures were enrolled for this study prospectively. The eligible patients were randomly assigned to either group A or B. Group A received lansoprazole 30 mg bid, amoxicillin 1.0 g tid and rifabutin 150 mg bid during 7 days, whereas group B received lansoprazole 60 mg bid, amoxicillin 1.0 g tid and rifabutin 150 mg bid during 7 days. Results: In group A, H. pylori eradication was achieved in 25 (78.1%) of the 32 patients in the ITT analysis and in 25 (80.6%) of the 31 patients in the PP analysis. In group B, H. pylori eradication was achieved in 26 (96.3%) of the 27 patients in the ITT analysis and in 27 (100%) of the 26 patients in the PP analysis. There was statistically significant difference between the two groups in terms of the eradication rates in PP analysis ( p  = .047), whereas a marginally statistical significance wasf ound in terms of the eradication rates in ITT analysis ( p  = .051). Reported side effects were mild, and treatment was well tolerated. No major changes in physical examination or in standard laboratory parameters were observed after treatment. Conclusions: Rifabutin‐based high‐dose proton‐pump inhibitor (PPI)‐combined therapy as empirical rescue treatment is more effective than standard dose PPI‐combined rifabutin‐based therapy, safe and best tolerable in third‐line therapy in the Korean population. The key to successful rescue therapy with rifabutin–amoxicillin–PPI regimen may be to increase doses of PPI.